Determinants of uptake and maintenance of active commuting to school. (July 2016) - Murtagh, Elaine M.; Dempster, Martin; Murphy, Marie H.
Abstract: The objective was to identify determinants of uptake and maintenance of active school travel (AST) over 4 years in children aged 9 at baseline. Data from wave 1 (n=8502) and 2 (n=7479) of the Growing Up in Ireland study were analysed. At 9- and 13-years 25% and 20% engaged in AST. Children were more likely to maintain or take-up AST if they lived in an urban area. Change in distance to school influenced both maintenance and adoption of AST, with a negative impact seen for increased distance between 9 and 13 years and a positive impact seen for decreased distance. Some factors which predict uptake and maintenance of AST are modifiable and can inform intervention development. Highlights: Determinants of uptake and maintenance of active commuting to school were examined. The majority of children passively commuted to school at 9 (75%) and 13 years (80%). The associations between predictor variables were generally weak. Maintenance of active travel was less likely to occur when distance to school increased. Taking up active travel is most likely to occur when distance to school decreases.